How CEO hubris affects corporate social (Ir)responsibility - Tang, Yi (2014)
Grounded in the upper echelons perspective and stakeholder theory, this study establishes a link between CEO hubris and corporate social responsibility (CSR). We first develop the theoretical argument that CEO hubris is negatively related to a firm’s socially responsible activities but positively related to its socially irresponsible activities. We then explore the boundary conditions of hubris effects and how these relationships are moderated by resource dependence mechanisms. With a longitudinal dataset of S&P 1500 index firms for the period 2001-2010, we find that the relationship between CEO hubris and CSR is weakened when the firm depends more on stakeholders for resources, such as when its internal resource endowments are diminished as indicated by firm size and slack, and when the external market becomes more uncertain and competitive. The implications of our findings for upper echelons theory and the CSR research are discussed.